SIYASAH DUSTURIYYAH DAN KEPASTIAN HUKUM DALAM PASAL 59 PERATURAN PEMERINTAH NOMOR 35 TAHUN 2021 - Ramadani Siregar (Universitas Muhammadiyah Tapanuli Selatan, 2023)
This research is motivated by the existence of a derivative regulation from the work copyright law, namely government regulation number 35 of 2021 which has caused a polemic, namely regarding the determination of employment regarding severance pay. Stating that the amount of severance pay given by UMKM entrepreneurs is based on an agreement between the employer and the worker. This causes article 59 to look vague and contains a lawsuit, because severance provisions are not stated in the provisions and open up opportunities for unilateral determination of severance pay by the employer. This type of research is descriptive-analytical library research and uses a juridical-normative approach. The primary legal materials used are the Job Creation Law of 2020 and Government Regulation Number 35 of 2021. Secondary legal materials used are the Koran and hadith, fiqh, books, journals. The results of this study are that Government Regulation Number 35 of 2021 has not been able to provide legal certainty for MSME workers because according to labor regulations the agreement between employers and workers is not sufficient because severance pay must comply with existing provisions, and has violated the principle of labor protection and is contrary to law work copyright. As with siyāsah dustūriyyah, in essence the relationship between the government and the people and the protection of people's rights must be able to provide protection, namely protection of their lives.